2012
DOI: 10.1021/ja211032m
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry-Dependent, Mechanoresponsive Supramolecular Host Assemblies for Fullerenes: A Guest-Induced Enhancement of Thixotropy

Abstract: Self-assembly behaviors of a series of systems (G1, G2, and G3) possessing same organic building blocks based on a substituted anthracene have been investigated in decalin. G2 and G3 are dominated by head-to-tail (ht) and head-to-head (hh) type dimers of G1, respectively. G1 gives a thermoresponsive gel that behaves ideally, showing frequency-independent elastic and viscous moduli. Interestingly, G2 produces a thixotropic gel that shows the signature of structural relaxation, signifying the dynamic nature of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 64 publications
0
41
0
Order By: Relevance
“…This kind of propensity to break down into smaller fragments is characteristic of thixotropic 15 behaviour and offers an explanation of the shear thinning response of the material. 54,[56][57][58] Mechanical agitation results in break-down of the fibres into individual short lengths of fibre and hence loss of network stability. On standing the fibres reassemble into a sample-spanning network.…”
Section: Resultsmentioning
confidence: 99%
“…This kind of propensity to break down into smaller fragments is characteristic of thixotropic 15 behaviour and offers an explanation of the shear thinning response of the material. 54,[56][57][58] Mechanical agitation results in break-down of the fibres into individual short lengths of fibre and hence loss of network stability. On standing the fibres reassemble into a sample-spanning network.…”
Section: Resultsmentioning
confidence: 99%
“…[415][416][417] The magnitude of a thixotropic response may be modified with the use of additives that interact strongly with the gelator, 417 or by altering the aggregation environment or type of stress applied. In one notable study, co-gels of a pyridyl bis(urea) with dicarboxylic acids were found by Liu and Steed to reform after mechanical disruption, but become non-thixotropic upon exposure to heating, high pH or prolonged sonication.…”
Section: Gels Under Stressmentioning
confidence: 99%
“…In another remarkable work by the Shinkai research group, self‐assembling behaviour of a series of systems consisting of the stereoisomers of dianthracene‐based molecules (Figure ) in decalin has been explored, and their dynamic behaviours were closely monitored with the help of rheology and microscopy experiments . The dianthracene derivatives were obtained by the photoisomerization of the corresponding monomer .…”
Section: Behaviors Of Smgs Under Shear: Non‐healable and Healable Smgsmentioning
confidence: 99%